Zoogeografia de los gastrópodos terrestres de la región oriental de San Luis Potosí, México - Correa Sandoval, Alfonso (Revista de Biología Tropical, 1999)
The land snails of the eastern regíon of San Luís Potosí, México were surveyed (June, 1995 - August, 1996). This regíon has much topographic and climatic variatíon. Samples (161) were obtained in 48 localities. The main zoogeographíc groups of were the endemic (32.18%: 28 species and three subspecies) and the neotropical (27.59%: 24 species and five subspecies) gastropods. The family Spiraxidae has the largest number of endemic species ( 16). The Eastern Sierra Madre has the 1argest number of species in the region